2020
DOI: 10.37314/jjem.2020.040101
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Natural Convection and Radiation in a Moving Radial Porous Fin

Abstract: The analysis of the heat transfer of the moving porous radial fin with natural convection and radiation effect has been carried out. Here, Newton's law of cooling, Fourier's law of conduction and Stefan-Boltzmann's law of radiation were considered to formulate the fin model. The generated governing equation was solved numerically using shooting technique based the fourth-fifth order Runge Kutta Fehlberg method. The resulting dimensionless parameters affecting the thermal performance of the fin were analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In practice, the extended surfaces are attached to heat transfer devices and components to facilitate the rate of heat transfer from the prime surface. Such an important passive method of heat transfer enhancements has provoked several studies over the past decades [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,...…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the extended surfaces are attached to heat transfer devices and components to facilitate the rate of heat transfer from the prime surface. Such an important passive method of heat transfer enhancements has provoked several studies over the past decades [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,...…”
Section: Introductionmentioning
confidence: 99%
“…A DTM study was conducted by [27] to evaluate the extreme heat transfer rate of annular fins under radiation effect. The numerical investigation of a radiating radial-shaped porous fin subject to convection and motion has been conducted [28][29][30]. It is observed that the higher values of the convective parameter and the radiative parameter improve the rate of heat transfer from the fin surface.…”
mentioning
confidence: 99%